Influence of physical fitness on special judo fitness test performance: a multiple linear regression analysis - Lopes-Silva, J. P.; Panissa, V. L. G.; Julio, U. F.; Franchini, E. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to identify the physical fitness variables that best predict Special Judo Fitness Test (SJFT) performance. Thirty-five male experienced judo athletes took part in this study. All athletes performed 5 tests: upper- and lower-body cycle ergometer graded exercise tests; upper- and lower-body Wingate tests; and SJFT. The peak oxygen consumption (Vo2peak), maximum heart rate (HRmax), maximum aerobic power, and the variables corresponding to onset blood lactate accumulation (OBLA) were determined during the graded exercise tests. For the Wingate tests, peak power (PP) and mean power were used. Furthermore, the total number of throws, heart rate (HR) immediately and 1 minute after, and SJFT index were calculated. Four separated forward multiple linear regressions (forward model) were used to identify the physical fitness variables that best explained the SJFT variables. Upper-body Vo2peak (ml/min/kg) explained 27% of variance in the total number of throws, whereas an additional 7% was explained by upper-body PP. Upper-body HRmax explained 46% of the variance in the HR immediately after the SJFT, whereas lower-body HR at OBLA accounted for an additional 8%. Lower-body HRmax explained 21% of the variance in the HR 1 minute after the SJFT, whereas peak lactate ([La-]peak) after the lower-body graded exercise test accounted for an additional 12%. Upper-body Vo2peak (ml/min/kg) alone accounted for 15% of the variance in the SJFT index. Based on these results, the data suggest that physical fitness variables, derived from upper- and lower-body aerobic and anaerobic tests, have a small ability to predict the SJFT variables.